Adsorption of lead (II) by a non-living algal biomass / Mudher A. Hussein - Mudher, A. Hussein (2010)
Conventional techniques for removing dissolved heavy metals are only practical and cost-effective when applied to high strength wastes with heavy metal ion concentrations greater than 100 ppm. The possibility of using a non-living algal biomass to solve this problem was studied. Lead(II) was used in this study because it has been reported to cause several disorders in human. The non-living algal biomass was obtained from the filamentous green alga Spirogyra neglecta. The effects of initial concentration and contact time, pH, and temperature on the adsorption of lead(II) by the non-living algal biomass were studied. The equilibrium isotherms and kinetics were found from batch adsorption experiments. The surface characteristics of the non-living algal biomass were examined using scanning electron microscope and Fourier Transformed Infrared Spectrometer. Langmuir, Freundlich models were applied to describe the adsorption isotherms of the metal ions by S. neglecta biomass. Langmuir model is more closer to the equilibrium data than the Freundlich isotherm. The kinetics of adsorption was found to follow the pseudo-second-order kinetic model. The adsorption of lead(II) by native non-living biomass was rapid reaching equilibrium within one hour of contact time. The effects of solution pH and temperature on adsorption equilibrium were investigated and the results indicated that adsorption of lead(II) by S. neglecta biomass increased with increasing pH and temperature. The calculated thermodynamic parameters, ΔG◦, ΔH◦ and ΔS◦ showed that the adsorption of lead(II) ions onto S. neglecta was feasible, spontaneous and endothermic under examined conditions. iii The maximum adsorption capacity (qmax) of S. neglecta biomass was found to be 132 mg/g form experimental data.